Digital Governance Policy Implementation Model Through Electronification of Land and Building Acquisition Fees (E-BPHTB) at the Baubau City Regional Revenue Agency - Rahmawati, Rahmawati (Department of Public Administration, 2025)
The implementation of E-Government policies can improve policy performance through quality services utilizing digital-based information technology. The Baubau City Regional Revenue Agency utilizes technological developments by issuing the E-BPHTB Application. This application is implemented at BAPENDA to improve service performance in the field of taxation. The success of the implementation can be seen from the positive reactions shown by Taxpayers. Although many still have technological stuttering. This problem has not become serious, because BAPENDA Baubau City continues to strive to conduct socialization both directly and indirectly. This study adopts O'Jones' theory, the method used is qualitative descriptive research. Data collection techniques, namely by reducing which consists of; data reduction, and drawing conclusions. The results of the study indicate that the implementation of the Electronic policy (Land and Building Acquisition Fee) at Bapenda Baubau City is quite good, but not as expected: Organization in terms of budgeting, and methods are good but the human resources owned are still lacking, not adequate especially in the field of determination in the process of completing duties and functions. Interpretation related to the explanation of the substance and understanding of the objectives and targets of the E-BPHTB policy has not been as expected, even though it has received support for policies such as the PDRD Law, Regional Regulation No. 5 of 2011 concerning BPHTB as the basis for implementing the collection and management of BPHTB, public understanding is still low, only limited to socialization through electronic media and billboards, Standard Operating Procedures and work procedures for policies already have a measurable and transparent mechanism, the mechanism or procedure is very clear, this can be seen from the determination and processing of data through the E-BPHTB Application which is following the determination of BPHTB.